Developmental progression of lymphatic valve morphology and function - Davis, Michael J.; Zawieja, Scott D.; Yang, Ying (Frontiers in Cell and Developmental Biology, 2024)
Introduction: The bileaflet valves found in collecting lymphatic vessels and some veins are essential for maintaining a unidirectional flow, which is important for lymphatic and venous function. Under an adverse pressure gradient, the two leaflets tightly overlap to prevent backflow. Valves are proposed to share four main stages of development, based on images obtained from randomly oriented valves in fixed mouse embryos, with the best structural views obtained from larger venous valves. It is not known at what stage lymphatic valves (LVs) become functional (e.g., able to oppose backflow), although a requirement for stage 4 is presumed. Methods: To gain an insight into this sequence of events for LVs, we used Prox1CreERT2:Foxo1fl/fl mice and Foxc2CreERT2:Foxo1fl/fl mouse models, in which deletion of the valve repressor factor Foxo1 promotes the development of new LVs in adult lymphatic vessels. Both strains also contained a Prox1eGFP reporter to image the lymphatic endothelium. Mesenteric collecting lymphatic vessels were dissected, cannulated, and pressurized for ex vivo tests of valve function. LVs at various stages (1–4 and intermediate) were identified in multi-valve segments, which were subsequently shortened to perform the backleak test on single valves. The GFP signal was then imaged at high magnification using a confocal microscope. Z-stack reconstructions enabled 1:1 comparisons of LV morphology with a quantitative measurement of back leak. Results: As expected, LVs of stages 1–3 were completely leaky in response to outflow pressure elevation. Stage 4 valves were generally not leaky, but valve integrity depended on the Cre line used to induce new valve formation. A high percentage of valves at leaflet an intermediate stage (3.5), in which there was an insertion of a second commissure, but without proper luminal alignment, effectively resisted back leak when the outflow pressure was increased. Discussion: Our findings represent the first 3D images of developing lymphatic valves and indicate that valves become competent between stages 3 and 4 of development.